Estimating the impact of monetary policy on inequality in China - José R. Sánchez-Fung (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​The paper estimates the impact of monetary policy on income inequality in China. The empirical modelling finds that a battery of monetary indicators, including a monetary overhang measure derived from a money demand equation, and the change in the unemployment rate lead to increases in the Gini coefficient. However, only unemployment is statistically significant. The lack of significance of the monetary indicators is robust to alternative specifications with variability in nominal aggregate demand instead of unemployment.
URN:NBN:fi:bof-201505201211
Keywords: E52; D31; 330